Identifikasi Karakteristik yang Mempengaruhi Kesuksesan Agen dan Atribut Asuransi yang Mempengaruhi Nasabah Masuk AJB Bumiputera 1912 Cabang Kediri - Ana Kusumawati; Roni Zakaria R.; I Wayan Suletra (Performa: Media Ilmiah Teknik Industri, 2004)
One of the developing service industries developing in Indonesia economy which is undergoing crisis is insurance industry, whose productivity and business quality are depended on agents’ capability as the main doer who are corresponding with marker and characteristic from this insurance. This research attempts to find out agent’s profile and characteristic, perception given from customer and also insurance’s attributes that influence a customer to join.The measurement used on this research is Likert scale with the valid questionnaires distributed to 117 respondents agents and 46 respondents customers from AJB Bumiputera 1912 branch Kediri. The results shows that successful agents’ profile generally women(65,12%), age between 35-50 years old(75%), come from East Java(58,26%), married(65,48%), have S1 degree(85,71%), and experience on this field more than 6 years(88%). By using discriminate Analysis it results that successful agents have knowledge and higher assertiveness than less successful agents, but owning lower recognition motivation. According to the customer, there is no difference between successful and less successful agents. By using Pareto diagram, we can conclude that agents are the most important attribute that influence customer to join with the insurance.